Information about conservation status is more important than species appearance in the species preferences of potential conservation donors. (11th September 2022) - Papworth, Sarah; Curtin, Polly
Summary: There are huge differences in the conservation support and attention received by different species, perhaps because of human preferences for specific aesthetic traits, such as body size and colouring. If there are such inherent human preferences, then new flagship species should be aesthetically similar to existing successful flagship species and conservation campaigns should not feature less attractive species. However, cultural preconceptions about species and the covariance of traits make it difficult to determine the role of aesthetic traits. Both of these problems can be overcome with imaginary animals. If preferences for certain species traits are inherent in the human psyche, then the same preferences should be found in both real and imaginary animals. Using an online survey with US participants, we find that aesthetic traits are associated with preferences for real but not imaginary animals. For both real and imaginary animals, small and declining populations are preferred. We therefore suggest that organizations should not reject potential flagship species based on appearance. Consistent preferences for poor conservation status and the ability to use our results to predict donations to real animal species suggest that conservation support for specific species could be encouraged if organizations communicate information regarding population sizes and trends.